â€œI Employed My Own Strategyâ€: Exploring Primary Headteachersâ€™ Organisational and Professional Socialisation (Malaysian Journal of Learning and Instruction, 2018)
Purpose â€“ The main purpose of this study was to explore primary headteachersâ€™ perceptions of their professional and organisational socialisation within their novice years as school leaders. There is a lack of studies exploring primary headteachersâ€™ socialisation within the Malaysian primary education context. Methodology â€“ A total of nine primary headteachers from three states were purposely selected and interviewed to obtain their perceptions on the professional socialisation they received before and after their appointment and the strategies that they employed within their organisational socialisation process. Findings â€“ The study revealed that the primary headteachers employed their own organisational socialisation strategies in order to be accepted as a new member of the school. These were relatively diverse but accorded with their schoolâ€™s values and culture. However, in terms of their professional socialisation, there were various findings: some mentioned the lack of support programs while others acknowledged receiving quite helpful programmes within their initial years of headship. The findings and the implications for the improvement of primary headteachersâ€™ socialisation are discussed. Significance â€“ This study provides supplementary literature that explores primary headteachersâ€™ organisational and professional socialisation within the Malaysian schooling context. This study notes some practical and theoretical implications for improving the prospective headteachersâ€™ training and their leadership development which aim to enhance the leadership qualities of future primary school leaders.